The Comparative Antimicrobial Effects of Ocimum basilicum Essential Oil in a Pure Form and Exposed to an Electric Field - Camelia Scheau; Flore Chirilă; Alina Petrache Mornea; Viorel Cornel Pop; Mădălina Cosovanu; Svetlana Micle; Teoodora Morar; Nicodim Fit; Horea Criveanu (Agricultura, 2021)
Abstract. Lately, essential oils have started to receive an increased attention as well from the prime consumers as from the scientific community, as people are beginning to be more interested to invest in a healthy lifestyle. Their complex composition grants them multiple effects including antibacterial, antiviral and antifungal effects, which led them to be envisioned as a valuable alternative for the extensive use of antibiotics, as bacteria started to develop resistance and become more difficult to treat. In this study we compared the antibacterial and antifungal effects of basil essential oil and basil essential oil exposed to an electric field on six bacterial strains and one strain of C. albicans. To meet our objective, we’ve used the agar diffusion method. Our results showed that basil essential oil has a mild inhibitory effect on most of the bacteria and on C. albicans. Additionally, the basil essential oil exposed to the electric field mostly kept the same profile, even though it proved that it caused a slight decrease in the values of the inhibition potential of basil essential oil, except for S. enteritidis, where it showed an increase in its antibiotic capacity.